GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR YIELD AND ITS COMPONENT TRAITS IN GERMPLASM LINES OF RICE (Oryza Sativa L.) - and R. ABDUL FIYAZ, D. SHIVANI, FARZANA JABEEN, K. SUPRIYA R. M. SUNDARAM, J. ARAVIND KUMAR (The Journal of Research, PJTSAU, 2021)
The present investigation was carried to know the extent of genetic variability in sixty-five germplasm lines of rice collected from all over India, for yield and yield attributing characters. Analysis of variance revealed highly significant differences for all the 10 characters, indicating the presence of genetic variability among the genotypes. The present investigation revealed that the estimates of PCV were slightly higher than GCV for all the characters studied indicating less influence of environmental factors on the expression of traits and the possibility for genetic improvement through direct selection for these traits. The magnitude ofPCV and GCV estimates were moderate for three traits viz., days to 50% flowering, plant height, panicle length, total number of tillers per plant, effective number of tillers per plant and test weight, indicating the influence of environment rather than the genotype alone. The heritability and genetic advance estimates were moderate for panicle length and high for all the other traits viz., days to 50% flowering, plant height, total number of tillers per plant, effective number of tillers per plant, panicle weight, number of filled grains per panicle, number of unfilled grains per panicle, test weight and single plant yield indicating the influence of additive gene action, as such selection would likely be effective for improvement of these traits.